The impact of legislation : a critical analysis of ex ante evaluation - Verschuuren, Jonathan (Martinus Nijhoff Publishers, 2009)
Ex ante evaluation of legislation has become an established rationalisation of legislative processes. Legislators and the public at large demand fresh laws to have a particular effect and no unwanted side effects. This book discusses the pros and cons and the opportunities, limitations, and challenges of ex ante assessment of legislation.